2013
DOI: 10.1080/10408398.2011.560296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Pressure on Physicochemical Properties of Meat

Abstract: The application of high pressure offers some interesting opportunities in the processing of muscle-based food products. It is well known that high-pressure processing can prolong the shelf life of meat products in addition to chilling but the pressure-labile nature of protein systems limits the commercial range of applications. High pressure can affect the texture and gel-forming properties of myofibrillar proteins and, hence, has been suggested as a physical and additive-free alternative to tenderize and soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(35 citation statements)
references
References 129 publications
0
28
0
7
Order By: Relevance
“…On the other hand, a substantial decrease in denaturation enthalpy of surimi prepared from prerigor Tilapia fillet as compared with postrigor Tilapia fillet that was also reported by Park et al [31]. Changes in the protein thermal profile in the postrigor state can be attributable to the biochemical, metabolic, and microbiological changes experienced by the muscles during the rigor resolution stage (Buckow et al 2013). The HHP treatments had a marked influence on the thermal stability of muscle proteins.…”
Section: Thermal Analysismentioning
confidence: 74%
“…On the other hand, a substantial decrease in denaturation enthalpy of surimi prepared from prerigor Tilapia fillet as compared with postrigor Tilapia fillet that was also reported by Park et al [31]. Changes in the protein thermal profile in the postrigor state can be attributable to the biochemical, metabolic, and microbiological changes experienced by the muscles during the rigor resolution stage (Buckow et al 2013). The HHP treatments had a marked influence on the thermal stability of muscle proteins.…”
Section: Thermal Analysismentioning
confidence: 74%
“…In the last two decades, many studies have been performed to understand the effects of HPP on meat quality parameters. These effects have also been comprehensively reviewed by many researches (i.e., Bajovic et al, ; Buckow, Sikes, & Tume, ; Sikes & Warner, ; Simonin, Duranton & de Lamballerie, ; Sun & Holley, ). In case of pork meat, one of the most important quality traits is postmortem pH decline and the extent to which it drops.…”
Section: Introductionmentioning
confidence: 99%
“…Colour changes due to oxidation of ferrous myoglobin into ferric metmyoglobin. To reach microbial inactivation in meat, usually pressure above 400 MPa is applied, as the result of such pressure increase, meat discoloration occurs due to the protein denaturation (Wackerbarth et al, 2009) It has often been reported that even by application of pressure above 200 MPa drastically changes the appearance of red meat within a few minutes of treatment at low temperatures (Tintchev et al, 2010;Buckow, 2013). Most studies report increase of lightness (L*) in the pressure range 200-350 MPa turning red colour of meat into a paler pink, redness (a*) is observed to decrease in values at 400-500 MPa, resulting in a greybrown meat with a cooked-like appearance, however, this is the more variable parameter and dependent on experimental design (i.e., type of meat, minced or whole muscle, and HPP conditions), and yellowness (b*) either increases or is not affected…”
Section: Effect Of Hpp On the Colour Of Meatmentioning
confidence: 99%
“…Lipid oxidation is not usually evident immediately after HPP but may become evident during chilled storage. Such oxidation affects quality through flavour deterioration (rancidity), colour changes, loss of nutritive value, and alterations of textural and functional properties through associated protein denaturation(Fuentes et al, 2010;Buckow, 2013). There are suggested possibilities to inhibit the lipid oxidation by limiting oxygen availability in the packaging, use of antioxidant active packaging or use of different antioxidants derived from natural by-products and their combination(Mariutti et al, 2008;Bolumar et al, 2011;Alves et al, 2012).…”
mentioning
confidence: 99%